Is Natural Solar Photolysis Effective for the Removal of Antibiotics and Pathogens from Waste Stabilization Pond? - Lima, Karla V.L. [UNESP]; de Jesus, Jany H.F. [UNESP]; Bronzel Junior, João L. [UNESP]; Nogueira, Raquel F.P. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2023)
This study aimed to investigate the occurrence of photolysis of two relevant antibiotics, sulfamethoxazole and trimethoprim, when present in a Waste Stabilization Pond and its disinfection under tropical irradiance. The influence of pH and matrix components, and the generation of photoproducts during solar exposure were evaluated. The pH-dependent speciation of antibiotics had a greater influence on the photolysis of antibiotics than the water matrix, with higher photodegradation at pH 4.1 than at pH 7.2. Trimethoprim was more susceptible to indirect photolysis, indicated by the steeper influence of the photosensitizers nitrate and humic acid compared to sulfamethoxazole. The photoproducts generated were persistent to photolysis and remained present in the samples up to 70 h irradiation. Wastewater disinfection was achieved after 70 h of solar exposure. Nonetheless, the exposure time required to remove at least 50% of sulfamethoxazole was on average 29 h and of trimethoprim 83 h, at the natural pH of the matrix (pH 7.2). Given that the residence time in Waste Stabilization Pond is 41 h, which corresponds to a maximum of 26 h solar irradiation, the exposure time in Waste Stabilization Pond is not sufficient to completely photodegrade antibiotics or disinfect the effluent, demanding further treatment.
Keywords: humic acid; nitrate; photodegradation; sulfamethoxazole; trimethoprim; wastewater treatment plant